PENGARUH RETURN ON ASSETS, EARNING PER SHARE DAN CURRENT RATIO TERHADAP KEBIJAKAN DIVIDEN PADA PT. TELEKOMUNIKASI INDONESIA - Fajar, Catur Martian; Ratnasari, Nira; Mutiara, Pipit (LPPM Universitas Adhirajasa Reswara Sanjaya, 2023)
Dividend policy is one of the financial decisions made by the company, where the dividend policy is a decision whether the profit the company makes at the end of the year will be distributed to shareholders in the form of dividends or will be held for capital increase for investment financing in the future. This study aims to determine the effect of return on assets, current ratio and earnings per share, both partially and simultaneously, on the dividend policy. At PT Telekomunikasi Indonesia, Tbk. period 2009-2018. The method used in this study is a quantitative method with an explanatory survey approach and a type of descriptive verification study. The results of this study show that the return on assets and earnings per share have a partial effect on the dividend policy, but the current ratio has no partial effect on the dividend policy. Simultaneous test results can be seen that there is a significant simultaneous effect between the return on assets, earnings per share and the current ratio on the dividend policy